1999
DOI: 10.1063/1.124104
|View full text |Cite
|
Sign up to set email alerts
|

(Ba,Sr)TiO 3 thin films with conducting perovskite electrodes for dynamic random access memory applications

Abstract: Interfaces and hence electrodes determine the performance of (Ba,Sr)TiO3 (BST) capacitors for ultralarge scale integration dynamic random access memories. Electrode materials forming a rectifying contact on BST drastically reduce the dielectric constant and hence the capacitance and charge storage density of the capacitor, when the dielectric thickness is reduced. This can limit the role of Pt as an electrode material for gigabit dynamic random access memories (DRAM). The conducting oxide, La0.5Sr0.5CoO3 (LSCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 9 publications
2
28
0
2
Order By: Relevance
“…So far, several different conducting oxides, e.g. YBa 2 Cu 3 O 7-d , SrRuO 3 , (La x ,Sr 1Àx )CoO 3 and (La x ,Sr 1Àx )MnO 3 , etc., are proved to be suitable electrodes in epitaxial heterostructures with BST layers and have been used extensively [6][7][8][9]. High-quality films grown on each other are easily obtained for those perovskitetype conducting oxides and ferroelectric layers because of their similar structures and small mismatches in lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several different conducting oxides, e.g. YBa 2 Cu 3 O 7-d , SrRuO 3 , (La x ,Sr 1Àx )CoO 3 and (La x ,Sr 1Àx )MnO 3 , etc., are proved to be suitable electrodes in epitaxial heterostructures with BST layers and have been used extensively [6][7][8][9]. High-quality films grown on each other are easily obtained for those perovskitetype conducting oxides and ferroelectric layers because of their similar structures and small mismatches in lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The leakage current density of BST thin film capacitor with LSCO electrode is found to be 200 nA/cm 2 at a bias voltage of 2 V for 800 nm thick BST film. The low leakage current density of the capacitor with LSCO electrode makes it a potential candidate for gigabit density memories [41].…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…Such materials include a large group of electro-ceramic materials comprising dielectrics, ferroelectrics, and piezoelectrics [1][2][3]. An example is (Ba,Sr)TiO 3 which possesses great potential for applications, in especially as high-permittivity dielectrics in micro-electronics or nonvolatile memory devices [4,5]. Researches on the structures and properties of these materials have shown that the shallow traps introduced by oxygen vacancies sensitively control material properties and device performance [6].…”
Section: Introductionmentioning
confidence: 99%